The unlikely pilgrimage of Harold Fry [compact disc, unabridged] - Joyce, Rachel (Random House Audio, 2012)
Harold Fry is convinced that he must deliver a letter to an old love in order to save her, meeting various characters along the way and reminiscing about the events of his past and people he has known, as he tries to find peace and acceptance.